The Divine Comedy - Alighieri, Dante (Oxford Oxford University Press, 2008)
Dante Alighieri's poetic masterpiece, The Divine Comedy, is a moving human drama, an unforgettable visionary journey through the infinite torment of Hell, up the arduous slopes of Purgatory, and on to the glorious realm of Paradise?the sphere of universal harmony and eternal salvation.
Includes bibliography
Keywords: Dante Alighieri, 1265-1321. Divina commedia